Analysis and Business Development Strategy of Sumil Kayu (A Study on Sumil Kayu PK. Putra Bakung in Jati Agung District) - Richi Ardiansyah; M. Oktaviannur (Cita konsultindo, 2025)
The increasing demand for timber due to population growth and technological advancements presents both opportunities and challenges for timber processing businesses. This study examines the development strategies of Sumil Kayu PK. Putra Bakung, a timber processing company in Jati Agung, Lampung Selatan, through SWOT analysis. The research aims to identify internal strengths and weaknesses as well as external opportunities and threats to formulate strategic recommendations. Employing a qualitative descriptive method, the study explores ways to enhance product quality, expand market reach, and adopt sustainable practices. The findings highlight key strategies to optimize business operations and improve competitive positioning (Afridhal, 2017).